The Microfacies Analysis of Mishrif Formation in Gharraf Oil Field - Nasser, Midhat; Nasser, Midhat; AL-Itbi, Nabaa (Iraqi Journal of Science, 2024)
Six main microfacies are identified which are Lime Mudstone, Bioclastic Wackeston, Bioclastic Packstone-Wackestone, Bioclastic Wackestone- Mudestone, Pelagic Mudstone–Wackestone, Bioclastic Packstone -Grainston Microfacies in addition to their associated depositional environment. The diagenesis process have affected the Mishrif rocks and played a role in deteriorating reservoir porosity in well Ga-2 and enhancing it in well Ga1,3.These processes include: cementation, micritization, recrystallization,dissolution,compaction pressure solution and dolomitization.